Spirokermeline: A Macrocyclic Spirolactone from Kermadecia elliptica Brongn. & Gris. Issue 42 (8th May 2018) - Khazem, Mays; Jolly, Claire; Gaslonde, Thomas; Massip, Stéphane; Negrier, Philippe; Espeau, Philippe; Michel, Sylvie; Litaudon, Marc
Abstract : Spirokermeline, a new macrocyclic compound derived from resorcinol, was isolated from Kermadecia elliptica, an endemic species of New Caledonia. The structure of spirokermeline was elucidated on the basis of spectroscopic analysis and X‐ray single‐crystal diffraction analysis. This is the first time that a 3 H, 3′ H ‐spiro[benzofuran‐2, 1′‐isobenzofuran]‐3, 3′‐dione was isolated from higher plants and only the second time that this scaffold was found in nature. A possible biosynthetic pathway is proposed. Abstract : The characterization of spirokermeline, a new macrocyclic spirolactone possessing an unprecedented spiro[butenolide]benzofuran‐3(2 H )‐one moiety, isolated from the bark of the New Caledonian endemic plant species Kermadecia elliptica (Proteaceae), is presented.